Capitalized family producers in a context of agrarian change - Bendini, Mónica (Universidad Nacional del Litoral, 2020)
The expansion of capitalism at the end of the last century has generated deep transformations in the structures and relations of production in agriculture. The process of agrarian restructuring accelerated the penetration of concentrated capital in the control of resources and boosted the advance of the production of raw materials and quality goods for export, affecting family production areas with different degrees of capitalization. The question that guides this article is how are capitalized family farmers inserted economically in the new social organization of agriculture, what are their strategies of persistence and how are they integrated into the mechanisms of capital accumulation. The empirical development addresses two cases of study. On the one hand, a rainfed area with recent agricultural expansion and substitution of activities (northern Córdoba); on the other, an area of ​​intensive agriculture under irrigation with conversion of a traditional activity (Alto Valle de Río Negro). The methodological strategy combines the analysis of secondary data with primary data from in–depth interviews.